THE IMPORTANCE OF MUSIC CULTURE IN PREPARING FUTURE PRIMARY TEACHERS FOR PEDAGOGICAL ACTIVITY (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This thesis discusses the importance of music and art, the subject of music methodology, which is offered as an elective subject to primary education students studying in higher education institutions, and how effective it is for students.